Trends in infective endocarditis mortality in the United Kingdom and EU 15+ countries between 1990–2019: an analysis of the Global Burden of Diseases database. (14th October 2021) - Hammond-Haley, M; Hartley, A; Delago, A J; Goodall, R; Marshall, D; Salciccioli, J D; Shalhoub, J
Abstract: Background: Infective Endocarditis (IE) is a relatively uncommon but lethal condition, with no convincing evidence to date of improving mortality trends (1). The epidemiology of IE is complex, driven by a wide range of constantly evolving factors. While marked international variation has been recently reported (2), temporal trends in mortality over recent decades remain unclear. Purpose: To describe trends in IE mortality in high income countries over the last 30 years. Methods: Age-standardised mortality rates (ASMR) for IE, stratified by sex, were extracted from the Global Burden of Disease (GBD) database (3) between 1990 and 2019. The United Kingdom and selected countries with comparable health expenditure (EU15+ countries) were included. Relative changes in ASMR over the observation period were determined and trends were analysed using Joinpoint regression analysis. Results: Between 1990–2019 ASMR from IE increased for both sexes in all included countries except Finland (−20.1% in males, −15.1% in females) and Austria (−8.98% in males, −22.6% in females). The largest increase in ASMR in males was observed in Greece (+197%), while the largest increase in females was observed in Italy (246%). Joinpoint regression analysis identified multiple significant trends within this observation period (Figure 1; clear squares indicate males, filled circles indicate females and lines represent modelled trends based on joinpoint data). At the end of the observation period the Netherlands had the highest ASMR in both males and females (2.28/100, 000 in males and 2.37/100, 000 in females), while Finland had the lowest ASMR in both males and females (0.45/100, 000 and 0.23/100, 000 respectively). Conclusions: Significant international variation in IE mortality rates were observed. While mortality from IE has generally increased over the last 30 years, recent data suggest this trend may now be plateauing or even reversing in certain countries. Funding Acknowledgement: Type of funding sources: None.